Effects of cranberry powder on the diversity of microbial communities and quality characteristics of fermented sausage - Yang, Le; Yan, Xinlei; Liu, Ting; Kang, Letian; Sun, Yufei; Gao, Xingyu; Zhao, Xin; Duan, Yan (Frontiers in Nutrition, 2023)
Fermented sausage is popular with many consumers because of its distinctive flavor, but the safety of it has attracted widespread attention. At present, nitrite is widely used in fermented meat products because of its ideal color and bacteriostatic effect, but nitrite can be transformed into nitrosamines, which cause strong carcinogenic effects. Therefore, it is urgent to actively explore safe and efficient nitrite substitutes. In this study, cranberry powder was selected as a natural substitute for nitrite during the production of fermented sausage due to its unique antioxidant and bacteriostatic properties. The results showed that adding an appropriate amount of cranberry powder (5 g/kg) promoted a better color of the fermented sausage and promoted the accumulation of aromatic compounds. Furthermore, Pediococcus and Staphylococcus became the dominant species, accounting for more than 90% in all samples. According to the Pearson correlation analysis, Staphylococcus and Pediococcus had positive effects on the quality characteristics of fermented sausage products. This study provided the latest information on the application of cranberry powder as a natural substitute for nitrite in the process of manufacturing fermented sausage, and it also introduced an advanced solution to improve the quality characteristics and safety of fermented sausage products during processing.